Effects of electroacupuncture on patients with chronic urinary retention caused by a lower motor neuron lesion: An exploratory pilot study - Zhou, Jing (Medicine (Baltimore), 2020)
Chronic urinary retention (CUR) is defined as a non-painful bladder that remains palpable or percussible after the patient has passed urine. Acupuncture may decrease PVR and improve bladder function in patients with neurogenic CUR. The aim of this study was to preliminarily observe the effectiveness of electroacupuncture (EA) for patients with CUR caused by a lower motor neuron lesion and to provide some therapeutic data for further study. This study was a pilot study of 30 patients with CUR caused by a lower motor neuron lesion. Patients were treated with EA for 12 weeks with 36 sessions of EA. Responders were defined as participants with a decline in postvoid residual urine (PVR) volume after spontaneous urination of ≥50% from baseline. The proportion of responders, change in PVR volume from baseline after spontaneous urination, and the proportion of patients with severe difficulty with urination, who required assistance with bladder emptying and with stool retention, were measured at weeks 4, 8, and 12. Thirty patients were included in this study, and 23 completed 12 weeks of treatment. The proportion of responders at weeks 4, 8, and 12 was 6.67%, 28%, and 43.48%, respectively. Decrease in PVR volume, compared with baseline, was significant at all asessment timepoints. The proportion of patients with severe difficulty with urination, who required assistance with bladder emptying and with stool retention, decreased after treatment. EA is a potential treatment for improving bladder function in patients with CUR caused by a lower motor neuron lesion.